Tannin agents from native Swietenia microphylla (sky fruit) for leather processing - Hashem, MA; Payel, S; Ali, MS; Bhowmik, P; Sahen, MS (Bangladesh Journal of Scientific and Industrial Research, 2023)
In leather processing, retanning is considered one of the most important steps which play a key role in the final leather. The retanning agent improves the required physicomechanical properties of the final leather. In this study, an alternative retanning agent is extracted from the native Swietenia macrophylla (sky fruit). The solvent extracted tannin from the sky fruit was characterized by Fourier Transform Infrared (FT-IR) speactroscopy. The tannin content of the sky fruit was 8.09%. The leather retanned with tannin extracted from sky fruit was compared with the conventional one. The physicomechanical properties-tensile strength, elongation at break (%), stitch tear strength, and shrinkage temperature fulfilled the requirements. The organoleptic properties of the retanned leather e.g., softness, fullness, grain smoothness, grain break, general appearance, and uniformity were evaluated in comparison with the conventional retanned leather. The extraction of retanning agent from the native sky fruit could be an alternative source of vegetable tannin which is locally and available. Bangladesh J. Sci. Ind. Res. 58(1), 01-08, 2023